PENGARUH PENERAPAN METODE HYPNOTEACHING TERHADAP HASIL BELAJAR SISWA PADA KELAS IV DALAM PEMBELAJARAN IPS DI SDN 133 PALEMBANG - Dian Merissa; Murjainah; Hermansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is motivated by the low academic achievement of students in Social Studies (IPS) at SDN 133 Palembang, highlighting the need for an innovative and effective teaching method. The purpose of this research is to determine the effect of the hypnoteaching method on improving the learning outcomes of fourth-grade students. This study employed an experimental approach using a one-group pretest-posttest design. The sample consisted of 30 fourth-grade students who received instruction through the hypnoteaching method. Data were collected using pretest and posttest scores and analyzed using the Paired Samples t-test, as the data were normally distributed. The results revealed a significant difference between the pretest and posttest scores, with t = -35.184, df = 29, and a significance level of p = 0.000 (p < 0.05). All students showed improved scores after the intervention. Therefore, it can be concluded that the hypnoteaching method has a significant effect on enhancing students’ learning outcomes in Social Studies. This method is a promising alternative for creating a more effective and engaging learning environment at the elementary school level